2014
DOI: 10.4028/www.scientific.net/amr.931-932.431
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Mix Proportion of Lightweight Concrete Containing Plastic Waste by Taguchi Method

Abstract: In this study, mix proportion parameters of lightweight concrete (LWC) containing ethyl vinyl acetate (EVA) plastic waste from footwear manufacture were investigated by employing Taguchis method and ANOVA statistics. The mixtures were designed in a L9 orthogonal array with four factors viz., water/cement, water content, EVA content and sand/cement. The results showed that EVA content and water/cement ratio had the significant effect on density and compressive strength of LWC. The density and compressive streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…The board band in range of 3399 cm-1 and 3637 cm-1 were attributed to O-H. After exposed at 800 °C, the change of cement paste structure was observed as shown in Figure 5 Figure 6 shows the characteristic of rubber crumb. The C-O was observed at 1415 cm − 1 [20]. The broad band in range of 3350-3550 cm −1 was assigned to O-H group of aromatic [21].…”
Section: Characterization Of Lwcs and Crumb Rubbermentioning
confidence: 95%
See 1 more Smart Citation
“…The board band in range of 3399 cm-1 and 3637 cm-1 were attributed to O-H. After exposed at 800 °C, the change of cement paste structure was observed as shown in Figure 5 Figure 6 shows the characteristic of rubber crumb. The C-O was observed at 1415 cm − 1 [20]. The broad band in range of 3350-3550 cm −1 was assigned to O-H group of aromatic [21].…”
Section: Characterization Of Lwcs and Crumb Rubbermentioning
confidence: 95%
“…Figure6shows the characteristic of rubber crumb. The C-O was observed at 1415 cm − 1[20]. The broad band in range of 3350-3550 cm −1 was assigned to O-H group of aromatic[21].…”
mentioning
confidence: 95%
“…EVA foam is used as padding in equipment for various sports such as ski boots, hockey, boxing, and mixed martial arts [15,16]. Researchers [17] found that EVA waste content and water/cement ratio were the most important mix proportion parameters of lightweight concrete containing EVA waste that affected density and compressive strength of lightweight concrete. The addition of plastic waste reduces the mechanical property and density of concrete due to lower strength and higher porosity of plastic aggregates [18,19].…”
Section: Introductionmentioning
confidence: 99%